2006
DOI: 10.1097/01.brs.0000247793.99827.b7
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential Fusion Improves Outcome in Comparison With Instrumented Posterolateral Fusion: Long-term Results of a Randomized Clinical Trial

Abstract: Circumferential lumbar fusion demands more extensive operative resources compared with posterolateral lumbar fusion. However, 5 to 9 years after surgery, the circumferentially fused patients had a significantly improved outcome compared with those treated by means of posterolateral fusion. These new results not only emphasize the superiority of circumferential fusion in the complex pathology of the lumbar spine but are also strongly supported in all of the validated questionnaires used in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 18 publications
8
61
1
2
Order By: Relevance
“…However, the low prevalence of severe ASD and the limited effect on outcome observed in this study do not seem to fully explain the previously demonstrated decline of outcome at long-term follow-up. In contrast to our results, two long term Danish studies on DDD without non-operated controls showed no deterioration of outcome 10-13 and 5-9 years post-operatively, respectively [1,51]. The reason for this discrepancy is unclear, but differences in diagnosis as well as type of fusion may apply.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the low prevalence of severe ASD and the limited effect on outcome observed in this study do not seem to fully explain the previously demonstrated decline of outcome at long-term follow-up. In contrast to our results, two long term Danish studies on DDD without non-operated controls showed no deterioration of outcome 10-13 and 5-9 years post-operatively, respectively [1,51]. The reason for this discrepancy is unclear, but differences in diagnosis as well as type of fusion may apply.…”
Section: Discussioncontrasting
confidence: 99%
“…4). Clinical result analysis demonstrated a significant improvement in function and lumbar and leg pain relief with a high rate of satisfaction similar to other series of degenerative lumbar surgery in younger patients [28].…”
Section: Discussionsupporting
confidence: 74%
“…In the absence of clinical differences, cages augmented with autogenous cancellous bone show similar mechanical characteristics to structural bone grafts [6,18,40]. Fusion rates of up to 100% have been achieved with these methods according to the literature [28,35,40].…”
Section: Introductionmentioning
confidence: 97%